WATER DIFFUSIVITY IN RHYOLITIC GLASSES AS DETERMINED BY IN SITU IR SPECTROSCOPY - Okumura S.; Nakashima S. (My University, 2004)
The dehydration rate of hydrous rhyolitic glasses at 475-875 °C was measured by in situ infrared (IR) spectroscopy in order to determine the diffusion coefficient of water in rhyolitic glasses. The IR spectra of glass thin sections were obtained at 90-s intervals during 90 min at high temperatures, and the change in absorbance at 3550 cm-1 corresponding to total water was monitored. The diffusion coefficients obtained from dehydration rates of the rhyolitic glasses are considered to be averaged value over the water-concentration profile in the sample. The averaged apparent diffusion coefficients increase with the initial total water content from 0.20 μm2 s-1 for 0.7 wt% to 0.37 μm2 s-1 for 2.8 wt% at 700 °C. The apparent activation energy for the diffusion of total water decreases with increasing initial water content from 112 ± 6 kJ mol-1 for 0.7 wt% to 60 ± 17 kJ mol-1 for 4.1 wt%. Assuming a linear relation between the diffusion coefficient of total water and the total water content, the diffusion coefficients at each initial total water content were also determined. The diffusion coefficients of total water at the water contents of 0.7 and 1.9 wt% and at 0.1 MPa were best fitted by ln D=[(12.9 ± 0.8) - (111 500 ± 6400)/RT] and ln D=[(10.6 ± 0.4) - (86 800 ± 2800)/RT], respectively, and are in agreement with previous data (D in μm2 s-1, T in K). The present in situ IR dehydration experiment is a rapid and effective method for the determination of water diffusivity at high temperatures.
Keywords: IN SITU IR SPECTROSCOPY; DEHYDRATION EXPERIMENT; WATER DIFFUSIVITY; WATER SPECIATION